A clinical investigation into the efficacy of miswak chewing sticks as an oral hygiene aid: A crossover randomized trial. Issue 2 (20th December 2020) - Rifaey, Noha; AlAdwani, Manar; Karched, Maribasappa; Baskaradoss, Jagan Kumar
Abstract: Objectives: This study evaluates the effect of using miswak chewing sticks on dental plaque, selected oral microbiota and gingival inflammation among patients with gingivitis. Methods: The study was a single‐centre, single‐examiner blind, randomized, crossover study. Twenty healthy participants were randomly assigned into two equal groups (n = 10). Group 1 were instructed to use both toothbrush and miswak (TB+M) for the first 2 weeks from baseline (T1) and only toothbrush for the next 2 weeks (T2); and Group 2, only TB during T1 and TB+M during T2. Gingival index (GI), plaque index (PI) and bleeding on probing (BOP) were evaluated at baseline (T0), T1 and T2 visits. Supra‐gingival plaque samples were taken at T0, T1 and T2. Quantification of Streptococcus mutans and Aggregatibacter actinomycetemcomitans from the supra‐gingival plaque samples were performed by real‐time polymerase chain reaction (qPCR). Results: The scores of GI, PI and BOP had significantly improved for both groups between T0 and T1. A significantly greater reduction in the percentage of sites with BOP was observed for TB+M group compared with TB group (TB+M group: from 32.2 to 14.93; TB group: from 34.00 to 26.0; p  = .014). At T2, TB+M group had significant improvements ( p  < .05) in the PI, GI and BOP scores compared with TB group. There was no significant difference in the microbial counts of S. mutans and A. actinomycetemcomitans between the two groups at the end of the study period. Conclusions: Oral hygiene and gingival health may be improved by complementing miswak chewing sticks with toothbrushing.